Pelatihan Laporan Keuangan Sederhana dan Pemasaran Produk Clay & Powder Melalui Media Sosial Pada Barbershop - Bhakti, Damba Satya; Wulandari, Ika (Yayasan Sagita Akademia Maju, 2024)
MSMEs are businesses carried out by individuals, groups, small business entities or households. Some MSME players have not made financial and marketing reports due to a lack of education and understanding about financial reports and product marketing. This community service aims to provide education to Mr. Tengku Fadli as owner of the Thanksfosolution barbershop in Sleman Regency regarding the importance of simple financial reports and product marketing on social media. . Simple financial reports help business people record income, expenses and profits regularly, so they can monitor business performance and improve decision making. Product marketing on Instagram social media helps promote clay and powder products for better marketing on social media. The implementation method used is to educate business actors and help create simple financial reports and market products on social media. The result of this activity is that MSMEs in Sleman Regency, specifically ThanksForsolution barbershops, can implement or create simple financial reports and market products on Instagram social media.